Fatigue fracture mechanism of sputtered AlSi alloy film by pulsating-tension cyclic loading testing - Shindo, Michiko; Yasugi, Daisuke; Saegusa, Hiroya; Tsuma, Hiroki; Nishiwaki, Tsuyoshi; Namazu, Takahiro (Thin solid films, 2024)
•Aluminum silicon (AlSi) and aluminum (Al) films are subject to fatigue test.•Adding silicon (Si) increases mechanical characteristics in Al film.•Fatigue crack propagation in AlSi film is 10 times slower than that in pure Al film.•AlSi film's fatigue crack propagates in a zigzag way while detouring Si segregation. This paper focuses on investigating the differences in fatigue fracture between sputtered aluminum silicon (AlSi) alloy and pure aluminum (Al) films by means of pulsating-tension cyclic loading tests. AlSi alloy film with 1.0 wt% (wt%) silicon (Si) and pure Al film are prepared at a substrate temperature of 450 ℃ and 260 ℃, respectively, by dc magnetron sputtering. After annealing those films at 490 ℃ under a hydrogen and nitrogen atmosphere for 1 hour, the tensile test specimens are prepared using semiconductor fabrication technologies. Quasi-static tensile tests measure the mean yield strength of 52 MPa and 33 MPa for AlSi and Al films, respectively, which are used as reference stress values for fatigue tests. During fatigue tests, a crack is introduced at the one-side edge of pure Al film specimen and propagates straightly to the other side, whereas a zig-zag crack is observed in AlSi alloy film. The crack propagation rate for AlSi film is around one-tenth of that for pure Al film. The mechanism of fatigue crack propagation is discussed based on element mapping results by energy dispersive X-ray analysis.